Morphometric Analysis of a Drainage Basin: A Study of Ghatganga River, Bajhang District, Nepal - Adhikari, Sandeep (The Geographic Base, 2020)
This study attempts to study the morphometric characteristics of the Ghatganga basin by using Geographical information system (GIS). This analysis has shown that the relation of stream order (U) and stream number (Nu) which gives a negative linear pattern that order increases with a decreasing number of stream segment of a particular order. Different morphometric parameters such as stream length (Lu), bifurcation ratio (Rb), drainage density (D), stream frequency (Fs), texture ratio (T), elongation ratio (Re), circularity ratio (Rc), form factor ratio (Rf), relief ratio (Rh) and river profile have revealed the basin has a dendritic pattern of drainage, indicating high relief and steep ground slope with less elongated young and mature landforms in which geological structures don’t have a dominant influence on the basin.